Pengaruh Budaya Organisasi, Teknologi Informasi dan Sistem Informasi Akuntansi Manajemen Terhadap Kinerja Manajerial pada Kampung Batik Laweyan - Denista, Nancy Eka Dara; Kurniawanto, Hudi (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study is motivated by the importance of improving managerial performance among business actors in Kampung Batik Laweyan as one of the strategic creative industry centers that contribute significantly to regional economic development. Rapid changes in the business environment require organizations to establish a strong organizational culture, optimize the use of information technology, and implement effective management accounting information systems to support managerial decision-making. The purpose of this study is to examine the influence of organizational culture, information technology, and management accounting information systems on managerial performance in Kampung Batik Laweyan. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to managers and business owners in Kampung Batik Laweyan selected using purposive sampling techniques. The collected data were analyzed using multiple linear regression analysis to determine the effect of each independent variable on managerial performance. The results indicate that organizational culture has a positive and significant effect on managerial performance, suggesting that organizational values, norms, and behavioral patterns enhance managerial effectiveness. Information technology also has a positive influence on managerial performance by improving the speed, accuracy, and quality of information used in decision-making processes. Furthermore, management accounting information systems significantly affect managerial performance by providing relevant, accurate, and timely information. The implications of this study suggest that strengthening organizational culture, enhancing the utilization of information technology, and developing integrated management accounting information systems are crucial strategies for improving managerial performance and increasing the competitiveness of batik enterprises in Kampung Batik Laweyan.